(untitled) (Advances in Tropical Biodiversity and Environmental Sciences, 2026)
The search for safer, more environmentally friendly ultraviolet (UV) filters has led to the exploration of bioactive plant compounds as alternatives to synthetic UV filters. This study evaluates the phytochemical composition and photoprotective potential of ethanol extracts from Annona muricata L. leaves as candidates for a natural photoprotective ingredient. The ethanol extract of soursop leaves contains polyphenolic secondary metabolites with a total phenolic content of 67.30 ± 1.27 mg GAE/g extract and a total flavonoid content of 63.62 ± 0.67 mg QE/g extract. These phenolic and flavonoid compounds contribute to photoprotective activity. With increasing extract concentrations, the SPF value rose significantly (p<0.05) to a maximum of 32.84 ± 0.75 at 1,000 µg/mL, suggesting a strong dose-response relationship between extract concentration and UVB protection (r ≈ 0.99). To achieve SPF 15, the soursop leaf ethanol extract required a concentration of 451.72 ± 1.09 µg/mL, while concentrations of 950.06 ± 1.42 µg/mL and 1,614.51 ± 1.37 µg/mL were needed for SPF 30 and SPF 50, respectively. The extract effectively blocks UVB radiation (measured by erythema percentage) and UVA radiation (measured by pigmentation percentage) at a concentration of 800 µg/mL. Overall, the ethanol extract of A. muricata L. leaves shows promise as a candidate for further evaluation as a natural photoprotective ingredient. These findings suggest that this extract could be developed as an active ingredient for multifunctional natural photoprotective formulations.